ANALYZING THE ROLES OF INDONESIAN IMMIGRATION AGAINST PANDEMIC - Rizqi Ganis Ashari; Dwi Bima Achmad Setyawan (Jurnal Analisa Sosiologi, 2021)
The spread of Coronavirus Disease 2019 (COVID-19) to various regions has initiated the government to formulate public policies to limit its spread. The restrictions to enter and exit a country's territory (lockdown), have become one of the public policies implemented by the governments. Despite the decision to apply lockdown, Indonesia has decided to apply a Large-Scale Social Restrictions (PSBB) program to overcome the transmission of COVID-19. The concrete impact of the implementation of the policy is dynamic changes in the Regulation of the Ministry of Law and Human Rights (Permenkumham) which acts as the basis for immigration practice. The study aimed to identify the role of Indonesian Immigration which stands on the four Laws of the ministerial regulations that were specifically formed in response to the spread of COVID-19. Based on a theoretical framework from the perspective of complexity and normative approaches using the Issue, Rule, Analysis/Application, and Conclusion methods, this study has identified a tendency for the role of Indonesian immigration to be adaptive following changes during a pandemic. The dynamics changes of ministerial regulations are formed through the interpretation of various facts. This interpretation has resulted in the gradual role of Indonesian Immigration which increasingly reinforces the regulation regarding the presence of foreigners in Indonesia at every change occurring in ministerial regulations. The implications regarding the adaptive nature of ministerial regulations are discussed further in this study by correlating the role of opinion leaders to minimizing negative images due to intensely changing policies. Keywords: Coronavirus Disease-19, Immigration Role, Public Policy, Complexity Perspective, Adaptive Regulation AbstrakPenyakit Coronavirus Disease 2019 (COVID-19) yang secara masif mewabah ke berbagai wilayah, mengakibatkan negara-negara di dunia merumuskan kebijakan publik untuk meminimalisir penularannya. Peraturan yang memperketat lalu lintas masyarakat untuk keluar dan masuk wilayah suatu negara (lockdown), menjadi salah satu opsi kebijakan publik yang banyak dipilih. Di tengah maraknya negara-negara di dunia menerapkan lockdown, Indonesia memilih opsi lain berupa Pembatasan Sosial Berskala Besar (PSBB) untuk mengatasi penularan COVID-19 di wilayahnya. Dampak kongkret dari diberlakukannya kebijakan itu adalah perubahan secara dinamis Peraturan Kementerian Hukum dan Asasi Manusia (Permenkumham) yang menjadi landasan atas berlangsungnya praktek keimigrasian. Penelitian ini kemudian bertujuan untuk mengetahui peran Imigrasi Indonesia yang berada pada empat Peraturan Menteri Hukum dan Hak Asasi Manusia yang secara khusus dibentuk untuk merespon COVID-19. Dengan menggunakan kerangka teoritik dari perspektif kompleksitas dalam pembuatan kebijakan publik dan pendekatan normatif dengan metode Issue, Rule, Analysis/Application, serta Conclusion, penelitian ini menemukan adanya kecenderungan peran Imigrasi Indonesia bersifat adaptif mengikuti perubahan lanskap sosial di saat pandemi. Dinamika perubahan peraturan menteri itu terbentuk melalui interpretasi terhadap berbagai fakta aktual. Hal ini berjalan melalui empat tahap: 1) pembelajaran, 2) negosiasi persetujuan, 3) transfer gagasan, dan 4) kontekstualisasi. Keempat tahap ini menghasilkan peran Imigirasi Indonesia yang bersifat gradual dan semakin ketat mengatur keberadaan orang asing di Indonesia di setiap perubahan peraturan menteri. Implikasi mengenai sifat adaptif peraturan menteri dibahas lebih jauh di penelitian ini dengan mengaitkan peran opinion leader untuk menimalisir citra negatif akibat kebijakan yang berubah secara intens. Kata Kunci: Coronavirus Disease-19; Peran Imigrasi, Kebijakan Publik, Perspektif Kompleksitas, Regulasi Adaptif